Effect of Pine Needle Fibers on Properties of Cementitious Mortars : Pine Needles-Reinforced Mortars - Zain-Ul-Abdin; Khitab, Anwar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The search for renewable and ecological resources of raw materials is beneficial for the progress of any technology including cementitious composites. With that intent, present work is aimed to evaluate the feasibility of pine needles (PN) in Himalayan range of Kashmir as natural fibers in conventional cementitious mortars. Three different lengths of PN, i.e. 13, 25 and 50 mm were chosen as case study. Doses were fixed as 1, 2, 3, 4, and 5% by mass of cement. The results were compared with those of control specimens. Specimens were evaluated in terms of flow-ability, surface saturated dry density (SSD), water absorption, compressive and flexural strengths and ultrasonic pulse velocity. The results show that cementitious mortars reinforced with 1% content and 13 mm length of pine needles offer the highest flow-ability and the lowest density. However, the highest strength and UPV and the lowest water absorption are achieved with 50 mm length of pine needles at 1% dosage. Based on the results, the optimum value of 1% pine needles fibers in cementitious mortars is recommended.